Evaluation of performance, safety, subject acceptance, and compliance of a disposable autoinjector for subcutaneous injections in healthy volunteers - Cecile Berteau; Florence Schwarzenbach; Yves Donazzolo; et al (Patient Preference and Adherence, 2010)
Cecile Berteau1, Florence Schwarzenbach1, Yves Donazzolo2, Mathilde Latreille2, Julie Berube3, Herve Abry1, Joël Cotten1, Celine Feger1, Philippe E Laurent11BD Medical Pharmaceutical Systems, Le-Pont-de-Claix, 2Eurofins Optimed Clinical Research, Gières, France; 3Statistics, BD Corporate, Franklin Lakes, NJ, USAObjective: A disposable autoinjector was developed for subcutaneous (SC) self-injection by patients with chronic diseases. To verify its performance and evaluate its acceptance, a clinical study was conducted in healthy volunteers, comparing SC injections performed by subjects using the autoinjector with SC injections performed by nurses using a syringe.Methods: This was a randomized, single-center, crossover study comparing SC self-injection using an autoinjector with SC nurse-administered injection using a syringe. Two volumes (0.2 mL and 1 mL) were injected into healthy volunteers. Study objectives included assessment of the accuracy and consistency of the volume injected by the injection systems, and skin reaction and pain associated with the injection. The fluid depot in the SC tissue layer was evaluated by ultrasound. Subject acceptance was evaluated using questionnaires on attitudes and emotions towards the injection technique, and challenged by seeking the subjects’ preferred system for a final study injection or future treatment.Results: A total of 960 injections (480 with autoinjector, 480 with syringe) were performed in 40 subjects. There were no significant differences in mean fluid leakage and injected volumes between the systems. Pain associated with the injection was significantly lower with the autoinjector than with the syringe. Local skin reaction at the injection site was overall satisfactory. Injections were appropriately performed by all subjects. At study end, all 40 subjects preferred the autoinjector for a final study injection and for future treatment.Conclusion: This study indicated that the autoinjector used by the subject was similar to a syringe used by a nurse in terms of performance and safety in administering the injections, and better in terms of pain, overall acceptance, and preference.Keywords: subcutaneous injection, autoinjector, self-injection, injection pain, preference, acceptance